Knowledge and Utilization Practices of Oral Contraceptive Pills among Females of Reproductive Age: A Community Based Study - Aguiyi-Ikeanyi, Chinelo Nneka; Agene, Moses Owoichoche; Ugochukwu, Ezinwanne Jane; Aroh, Obinna Jude (Indian Journal of Pharmacy Practice)
Introduction: There is still unmet need of contraceptives use among Nigerian females especially the younger females despite the existence of adolescent reproductive health policy in Nigeria. This study assessed the knowledge and the utilization practices of oral contraceptives among female of reproductive age resident in Karu community of Nasarawa State. Materials and Methods: This study is a cross sectional study using a convenient sampling method with the aid of a structured questionnaire which had three (3) sections. Section A is to obtain the respondents socio-demographic characteristics. Section B assesses the respondents’ knowledge of contraceptives. Section C assessed respondents’ Utilization practice of Contraceptives. Data obtained was analyzed using SPSS Version 21 statistical software. Descriptive statistics and inferential analysis were conducted to obtain the mean, and standard deviations. Chi square was used to obtain association between categorical variables and respondents’ socio-demographic characteristics. A p-value<0.05 was statistically significant at 95% CI. Results: Out of the 400 respondents, 197 (49%) were single while 19 (5%) were co-habiting. Most 129(32%) were within the age group of 25-30 years while only 128 (32%) of the respondents attained tertiary level of education. About 102 (25%) were civil servants while 159 (40%) practiced Islamic religion. Most (97%) of the respondents had good knowledge of oral contraceptives, however about 50.3% of the respondents had poor oral emergency contraceptives pill utilization practices. Conclusion: The female resident in Karu community of Nasarawa State had good knowledge of oral contraceptives, however their utilization practice of oral contraceptive pills was poor.
Keywords: Oral contraceptive; Emergency contraceptive pill; Knowledge; Utilization practice